Cultural and Wellness Tourism: The Potential of Yoga, Meditation and Self-Purification Ceremony - Ida Bagus Nyoman Mantra; I Nyoman Suparsa; Nengah Dwi Handayani (Soshum: Jurnal Sosial dan Humaniora, 2023)
Cultural and wellness tourism is one of the tourism assets that can be developed to support sustainable tourism. Yoga, meditation, and self-purification are components of Balinese culture that are practised by many Indonesians and foreigners alike. Yoga, meditation, and self-purification activities can be used to promote cultural and wellness tourism to attract domestic and foreign tourists. This research was conducted to determine whether yoga, meditation, and self-purification activities support cultural tourism in Bali. The research method used is a qualitative method where data were collected through interviews and field observations. The data were then analyzed descriptively. This study found that yoga, meditation, and self-purification activities can be used to promote cultural and wellness tourism in Bali. This research has implications that yoga, meditation, and self-purification activities can be designed to be used for sustainable cultural tourism activities and can also be used for attractive promotional media.